2021
DOI: 10.1002/jsfa.11602
|View full text |Cite
|
Sign up to set email alerts
|

Laminaria japonica fucoidan ameliorates cyclophosphamide‐induced liver and kidney injury possibly by regulating Nrf2/HO‐1 and TLR4/NF‐κB signaling pathways

Abstract: BACKGROUND: During clinical practice, cyclophosphamide (CTX) can lead to liver and kidney injury in vivo. In this study, we established a liver and kidney injury model by injecting CTX (80 mg kg −1 d −1 ) into male ICR mice, and then mice were treated with saline and fucoidan (20 or 40 mg kg −1 ), respectively. Subsequently, the liver and kidney toxicity indices, the expression levels of malonic dialdehyde (MDA), inflammatory factors, and the main protein levels of the Nrf2/HO-1 and TLR4/NF-κB pathways were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Many studies have shown the correlation between ROS, inflammatory cytokines, and NF‐κB signaling pathway (Li et al., 2021a). Simultaneously, some of nature products were confirmed to ameliorate liver injury by regulating NF‐κB signaling pathway (Tian et al., 2022; Zhao et al., 2021). For further screening of bioactive compounds of NE participating in NF‐κB pathway and alcoholic liver disease pathway against ALI, the compound‐target‐NF‐κB/alcoholic liver disease pathway network was established (Figure 3b and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown the correlation between ROS, inflammatory cytokines, and NF‐κB signaling pathway (Li et al., 2021a). Simultaneously, some of nature products were confirmed to ameliorate liver injury by regulating NF‐κB signaling pathway (Tian et al., 2022; Zhao et al., 2021). For further screening of bioactive compounds of NE participating in NF‐κB pathway and alcoholic liver disease pathway against ALI, the compound‐target‐NF‐κB/alcoholic liver disease pathway network was established (Figure 3b and Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…44 A study by Jung et al 45 also showed that NF-κB p65 acetylation is regulated through SIRT1, and they argued that SIRT1 activation may be a probable target in repairing cisplatin-induced kidney damage. In addition, Tian et al 46 informed that toxicity caused by CP was prevented via regulating the Nrf2/HO-1 and TLR4/ NF-κB signaling. We showed that in the CP-treated group, Nrf2 activation and SIRT1 levels decreased and NF-κB levels increased, whereas PEITC pretreatment caused the activation of Nrf2 and led to an elevation in the SIRT1 levels and inhibition of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Sections were washed with phosphate buffer saline (PBS) three times after each step. Sections were then stained with diaminobenzidine chromogen solution (DAB), and counterstained with Mayer’s hematoxylin [ 45 , 46 ], then dehydrated and mounted. Negative control sections were obtained by omitting the primary antibodies.…”
Section: Methodsmentioning
confidence: 99%